Combustion characteristics of tri-fuel (diesel-ethanol-biodiesel) emulsion fuels in CI engine with micro-explosion phenomenon attributes - Mukhtar N.A., M. (Elsevier Ltd, 2022)
Diesel engines are on the verge of extinction due to strict emission regulations. The current work is part of the initiative on the fuel-based modification for combustion, performance, and emissions improvement. The objective of the study was to investigate the combustion characteristics of tri-fuel emulsions with secondary atomization attribute known as the micro-explosion phenomenon. In this study, alternative fuel for CI engines called tri-fuel emulsions was prepared using Hielscher Ultrasonic Processor UP400S. Three different samples of tri-fuel emulsion, namely E5B5D90 (5 ethanol and 5 biodiesel), E10B10D80 (10 ethanol and 10 biodiesel), and E15B15D70 (15 ethanol and 15 biodiesel) were selected to be further investigated based on selection criteria which the same authors previously published. A single-cylinder diesel engine was set up to attain tri-fuel emulsions combustion characteristics. The combustion characteristics were investigated by installing Optrand fiber optic-based pressure transducer model Auto-PSI C82294-Q to obtain the in-cylinder pressure reading. The Indicated Mean Effective Pressure (IMEP), Coefficient of Variable (COV) of IMEP, Heat Release Rate (HRR), and Ignition delay were analyzed from the in-cylinder pressure. The average combustion characteristics result has offered a positive outcome when the engine was running with no load. The heat release rate and in-cylinder pressure of tri-fuel emulsion during the ignition delay period has exceeded that of diesel. The peak of heat release rate and in-cylinder pressure of the tri-fuel emulsions have improved compared to that of diesel. Â© 2021 Elsevier Ltd